2002
DOI: 10.1016/s0304-3959(02)00071-4
|View full text |Cite
|
Sign up to set email alerts
|

Inward currents in primary nociceptive neurons of the rat and pain sensations in humans elicited by infrared diode laser pulses

Abstract: Radiant heat is often used to study nociception in vivo. We now used infrared radiation generated by a diode laser stimulator (wavelength 980 nm) to investigate transduction mechanisms for noxious heat stimuli in acutely dissociated dorsal root ganglion (DRG) neurons of rats in vitro. The laser stimulator offered the unique opportunity to test whether the same stimuli also elicit pain sensations in humans. A specific heat-induced current (I(heat)) was elicited in six of 13 small DRG neurons (diameter < or =30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 43 publications
6
45
0
Order By: Relevance
“…This response pattern resembles that of heat-evoked currents (Greffrath et al 2002;Schwarz et al 2000;Vyklický et al 1999). Decreasing depolarizing generator current I heat leads in current-clamp mode to a reduction of membrane depolarization.…”
Section: Suppression Of Heat-induced Ap Discharges During Repetitive mentioning
confidence: 62%
See 1 more Smart Citation
“…This response pattern resembles that of heat-evoked currents (Greffrath et al 2002;Schwarz et al 2000;Vyklický et al 1999). Decreasing depolarizing generator current I heat leads in current-clamp mode to a reduction of membrane depolarization.…”
Section: Suppression Of Heat-induced Ap Discharges During Repetitive mentioning
confidence: 62%
“…In native DRG neurons, peak values of heat-evoked depolarizing currents vary greatly between 50 and 10,000 pA (Cesare and McNaughton 1996;Greffrath et al 2002;Kirschstein et al 1999;Liu and Simon 2000;Nagy and Rang 1999;Rau et al 2007;Reichling and Levine 1997;Vyklický et al 1999). These currents may or may not be sufficient to reach the threshold of APs (Scholz et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…8) Other experiments have indicated that brief high heating rate diode laser pulses can selectively activate myelinated Aδ fiber nociceptors in rats and produce pricking pain in humans, whereas low heating rate, longer pulses can preferentially activate unmyelinated C fibers in rats and produce burning pain in humans. [39][40][41][42][43] There is no evidence whether these different pulse parameters will differentially activate fibers in humans.…”
Section: Original Articlesmentioning
confidence: 99%
“…The authors noted that the temperature effects of irradiation were responsible for the outcomes of the experiments. A recent study showed that irradiation with a pulsed, near-infrared diode laser (l ¼ 980 nm and 4 ms to 400 ms pulse length) induced inward currents in dissociated cell cultures of nocioceptive rat dorsal root ganglion cells [46]. At the stimulation threshold fluence of 2.8 J cm À2 , they calculated a temperature of 42 C at the neurons.…”
Section: Direct Optical Stimulation Of Neural Tissuementioning
confidence: 99%